Handbook of prevention and intervention programs for adolescent girls - LeCroy, Craig W.; Mann, Joyce Elizabeth (Hoboken, N.J. : John Wiley & Sons, 2008)
Handbook of Prevention and Intervention Programs for Adolescent Girls presents the latest research, programs, and approaches that respond to the needs of todays adolescent girls. In this practical guide, editors Craig LeCroy and Joyce Mann have brought together a notable team of contributors to produce a resource with both diverse coverage and practical applications. Filled with helpful examples, this is an indispensable, hands-on resource for practitioners and students in mental health, education, and public policy.
Introduction : adolescent girls and the pathway to adulthood / Craig Winston LeCroy -- Universal prevention for adolescent girls : the Go Grrrls Program / Craig Winston LeCroy -- Developing friendships and peer relationships : building social support with the Girls Circle Program / Beth Hossfeld -- A dissonance-based intervention for the prevention of eating disorders and obesity / Heather Shaw and Eric Stice -- Preventing depression in early adolescent girls : the Penn Resiliency and Girls in Transition programs / Jane E. Gillham [and others] -- Preventing HIV among African American female adolescents : development and evaluation of a gender and culturally congruent prevention intervention / Gina Wingood [and others] -- Manifesting the strengths of rural Latina girls / Velia G. Leybas -- Athletes Targeting Healthy Exercise and Nutrition Alternatives : harm reduction/health promotion program for female high school athletes / Diane L. Elliot and Linn Goldberg -- Teens with anorexia nervosa : a family-based approach to treatment / Daniel le Grange and James Lock -- Incarcerated female teens and substance abuse : the Holistic Enrichment for At-Risk Teens (HEART) Program / Amelia C. Roberts and Chiquitia Welch -- Empirically validated approaches to family treatment for adolescent girls / Jacqueline Corcoran and Jane Phillips -- Mentorship : the GirlPOWER! Program / David L. DuBois [and others].
Includes bibliographical references and indexes.
Print version record.
John Wiley and Sons
Keywords: Teenage girls -- Services for -- United States -- Case studies; Social work with teenagers -- United States; Preventive health services -- United States -- Case studies; Preventive Health Services [MESH]; Preventive Health Services; Adolescentes -- Services -- v; Service social aux adolescents; z; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; POLITICAL SCIENCE -- Public Policy -- Social Security; Preventive health services; Social work with teenagers; Teenage girls -- Services for; United States; Weibliche Jugend; Psychosoziale Arbeit; USA; Case studies